Development of HOTS Science Test: Ethno-Science Technology Engineering and mathematics (STEM) based on Javanese Gamelan - N. A. Awaliyah; Y. Widiyawati; I. Nurwahidah (Universitas Negeri Yogyakarta, 2022)
Ethno-STEM is appropriate to accommodate High Order Thinking Skills (HOTS). The study aimed to develop an ethno-STEM-based HOTS science test instrument for Javanese gamelan musical instruments for junior high school students. The development research referred to the Thiagarajan 4-D (Four-D) development model with define, design, develop, and disseminate. The sample in this study was 24 students of VIII grades. The learning expert validation sheets, practitioner validation sheets, student questionnaires, and student ability test results were used in this particular research. The data analysis of the science test instrument feasibility showed that: (1) both experts’ and practitioners’ judgment with overall score classified into a very good category and students’ response classified into good categories; and (2) the reliability test showed a correlation coefficient of 0.8 so that it was declared as reliable. In short, the instrument based on Javanese gamelan Ethno-STEM instruments on Vibration and Sound Waves was appropriate to improve and optimize students' HOTS.